CCR6 controls autoimmune but not innate immunity‐driven experimental arthritis. Issue 11 (22nd August 2018) - Bonelli, Michael; Puchner, Antonia; Göschl, Lisa; Hayer, Silvia; Niederreiter, Birgit; Steiner, Guenter; Tillmann, Katharina; Plasenzotti, Roberto; Podesser, Bruno; Georgel, Philippe; Smolen, Josef; Scheinecker, Clemens; et al.
Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, characterized by synovial infiltration of various inflammatory cells. Chemokines are involved in controlling the recruitment of different cell types into the synovial membrane. The role of CCR6 in the development of arthritis so far remains unclear. In this study, we investigated the role of CCR6 in the pathogenesis of arthritis using three different murine arthritis models. Compared to WT animals, CCR6 −/− mice developed less clinical signs of arthritis in the collagen‐induced arthritis model but not in the K/BxN serum transfer arthritis model and in the human tumour necrosis factor transgenic arthritis model, suggesting a defect in adaptive effector functions but intact innate effector functions in the development of arthritis in CCR6 −/− animals. In line with this, anti‐collagen antibody levels were significantly reduced in CCR6 −/− mice compared with WT mice. Moreover, we demonstrate enhanced osteoclastogenesis in vitro in CCR6 −/− mice compared with WT mice. However, we did not detect differences in bone mass under steady state conditions in vivo between WT and CCR6‐deficient mice. These data suggest that CCR6 is crucially involved in adaptive but not in innate immunity‐driven arthritis. CCR6 or its chemokine ligand CCL20 might represent a possible new target for the treatment of RA.